DNA and RNA in the Context of the ‘Colloid-Coherence’ Paradigm of Cell Physiology - Jaeken, Laurent (Recent Research Advances in Biology Vol. 7, 2021)
There are by now direct observations of the complex colloid properties and phase-transition behaviour of cells; and observations of coherent behaviour. This compels to abandon the still reigning ‘membrane-pump-theory’ altogether, with all its ramifications, because it is based on the untenable physics of diluted solutions with a ‘steady state non-equilibrium’ bioenergetics as a result. It should be replaced by a new physiology founded on the physics of colloids, which enables coherent behaviour, a new ‘colloid-coherence’ view with a ‘low-entropy driven equilibrium thermodynamic’. Fortunately, such view exists already: it is fully elaborated in G.N. Ling’s ‘association-induction hypothesis’. This hypothesis quantitatively describes protoplasmic processes through a deeper understanding of how ensembles of protein, water, ions and controlling ligands operate as functional coherent ’nano-protoplasmic units’. This review is the first attempt to find out if this very general well-formulated hypothesis is also applicable to DNA and RNA.